(3GdLhGH GdQGFb aj JfRjg GdNGdb Yf eTGHgGJ GdeecfGJ hGdchf aj GdCMjGf hGdLgGJs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s ((3UdGM Hf eMeO Hf UdGM Hf Ydi Hf GdMSjf Hf YHO Gddg Hf jMji Hf MeRI s)
(3ChdgG (B:s
(3GdMeO ddg GdebOS ai PGJg Yf eTGHgI GdeecfGJ GdefRg ai UaGJg Yf eTGcdI GdeMOKGJ CeG HYO aEf GdHGYK Ydi gPG GdEedGA gh Cf HYV GdENhGf eecf jLH eQGYGI Mbg dOjGfJg SCdfi Yf CSFdI JJYdb HJfRjg Gddg s
(3BNQgG (B:s
(3agPG eG CQOfG PcQg ai gPg GdeSGFd Ydi LgI GdGNJUGQ hdYd Gddg Cf jTQM UOQg dagegG hjYbd eYGfjgG s
(3GdfSNI HgG MhGTs
(3GfJgi ef GdJCdja SfI (B702(3g`s
(3HgG fXGe GdJYbjHIs
(3fSNI eUMMI s
(3cJJ GdahGJM HGdSejc s
(3YdjgG Jedc eDQN SfI (B1304(3g` HGSe eMeO Hf SYjO GdYTGQi s
Keywords: (3GdJhMjO hGdedd hGdfMds